Proximal magnetometry in thin films using betaNMR. - Xu, M; Hossain, MD; Saadaoui, H; Parolin, T; Chow, K; Keeler, T; Kiefl, R; Morris, G; Salman, Z; Song, Q; Wang, D; MacFarlane, W (2008)
Low energy ion implantation of hyperpolarized radioactive magnetic resonance probes allows the NMR study of thin film heterostructures by enabling depth-resolved measurements on a nanometer lengthscale. By stopping the probe ions in a layer adjacent to a layer of interest, it is possible to study magnetic fields proximally. Here we show that, in the simplest case of a uniformly magnetized layer, this yields an unperturbed in situ frequency reference. We also discuss demagnetization contributions to measured shifts for this case. With a simple illustrative calculation, we show how a nonuniformly magnetized layer causes a strongly depth-dependent line broadening in an adjacent layer. We then give some experimental examples of resonance line broadening in heterostructures.